Chess and mathematical thinking in early childhood : a master move! - Dueñas Gómez, Olga Lucía; Guativa Quincosis, Yenith Carolina (Rastros Rostros, 2021)
This article shows the contributions to the development of logical mathematical competences through the approach to chess in early childhood, framed in the design and application of a pedagogical strategy based on the game, in order to strengthen the mathematical logical thinking of children. This research was developed taking into account the qualitative paradigm with a hermeneutic approach and type of descriptive research; the techniques used to collection of information were observation, interview, survey and use of documents. As a relevant result, it is found that chess fosters the knowledge of logical mathematical relations, spatial location, and identification of the characteristics of the objects, which worked in early childhood facilitate the subsequent formal learning of mathematics. Finally, it is concluded that the strategy contributes to the development of mathematical logical thinking, allowing the child to strengthen his competences from doing, knowing and being able to do.
Keywords: Chess; logical mathematical competence; pedagogical strategy; early childhood; constructivism